Playing position and the injury incidence rate in male academy soccer players - Hall, E. C.; Larruskain, J.; Gil, S. M.; Lekue, J. A.; Baumert, P.; Rienzi, E.; Moreno, S.; Tannure, M.; Murtagh, C. F.; Ade, J. D.; Squires, D.; Orme, P.; et al. (Journal of Athletic Training, 2022)
Context Whether playing position influences injury in male academy soccer players (ASPs) is unclear.